The Effects of Spinal, Inhalation, and Total Intravenous Anesthetic Techniques on Ischemia-Reperfusion Injury in Arthroscopic Knee Surgery. (20th February 2014) - Koşucu, Müge; Coşkun, İlker; Eroglu, Ahmet; Kutanis, Dilek; Menteşe, Ahmet; Karahan, S. Caner; Baki, Emre; Kerimoğlu, Servet; Topbas, Murat
Abstract : Purpose . To compare the effects of different anesthesia techniques on tourniquet-related ischemia-reperfusion by measuring the levels of malondialdehyde (MDA), ischemia-modified albumin (IMA) and neuromuscular side effects. Methods . Sixty ASAI-II patients undergoing arthroscopic knee surgery were randomised to three groups. In Group S, intrathecal anesthesia was administered using levobupivacaine. Anesthesia was induced and maintained with sevoflurane in Group I and TIVA with propofol in Group T. Blood samples were obtained before the induction of anesthesia (t 1 ), 30 min after tourniquet inflation (t 2 ), immediately before (t 3 ), and 5 min (t 4 ), 15 min (t 5 ), 30 min (t 6 ), 1 h (t 7 ), 2 h (t 8 ), and 6 h (t 9 ) after tourniquet release. Results . MDA and IMA levels increased significantly compared with baseline values in Group S at t 2 – t 9 and t 2 – t 7 . MDA levels in Group T and Group I were significantly lower than those in Group S at t 2 – t 8 and t 2 – t 9 . IMA levels in Group T were significantly lower than those in Group S at t 2 – t 7 . Postoperatively, a temporary 1/5 loss of strength in dorsiflexion of the ankle was observed in 3 patients in Group S and 1 in Group I. Conclusions . TIVA with propofol can make a positive contribution in tourniquet-related ischemia-reperfusion.